2023
DOI: 10.1007/s10286-023-00965-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep duration and muscle sympathetic nerve activity

Abstract: Purpose Sleep duration is associated with risk of hypertension and cardiovascular diseases. It is thought that shorter sleep increases sympathetic activity. However, most studies are based on acute experimental sleep deprivation that have produced conflicting results. Furthermore, there are limited data available on habitual sleep duration and gold-standard measures of sympathetic activation. Hence, this study aimed to assess the association between habitual sleep duration and muscle sympathetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…stemming from sympathetic hyperactivity [4][5][6]. However, our index of sympathetic modulations of the heart (LF/ HF ratio) was not associated with sleep duration regularity or the rise in systolic BP during exercise.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…stemming from sympathetic hyperactivity [4][5][6]. However, our index of sympathetic modulations of the heart (LF/ HF ratio) was not associated with sleep duration regularity or the rise in systolic BP during exercise.…”
mentioning
confidence: 63%
“… 4 Possible mechanisms that explain this phenomenon include augmented sympathetic activity and decreased baroreflex sensitivity that are reported to occur after sleep loss. 5 , 6 Thus, analyzing for sleep duration regularity may be a useful tool to capture the impact of intermittent nights of insufficient sleep on BP dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a decrease in brain glucose utilization, concomitant with the drop in cognitive performance that occurs with total sleep deprivation could potentially contribute to the disruption of whole-body glucose utilization (81). Researchers also have consistently shown that sleep restriction increases sympathetic nervous system activity (17,24,27,82,83), which is known to regulate insulin and glucagon secretion (84).…”
Section: Other Mechanismsmentioning
confidence: 99%